Electronic Tourist Guide in Malaysia by Using WAP Technology - Almuiet, Mohammad Zayed (2008)
With Electronic Tourist Guide in Malaysia by using WAP technology can be obtained easily way and flexibility to access the information at any time in any location. This research introduces a WAP application that provides the tourist with the service of the other information that most of the tourist needs it in order to reduce the time and the effort for them. By using this technology, tourist can easily get necessary information about the restaurant information, maps guide and other services by using the mobile device that help to save the time and effort on the tourists by check them enquires by mobile device.